Method of Identifying Matan Hadith Version of Salahudin bin Ahmad al-Idlibi - Muhammad Rifqy Farhanullah; Engkos Kosasih; Dadah, Dadah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article discusses the method of matan criticism or contemporary hadith redaction by Sheikh Salahudin bin Ahmad al-Idlibi in the book Manhaju Naqdi al-Matni 'Inda 'Ulama al-Hadith an-Nabawi. Explanation of the author's method of editorial criticism of the hadith in his essay as well as the criteria for accepting a hadith. This research uses a qualitative approach and applies content analysis methods. The data collection technique for this research uses library research, namely by collecting data sourced from books and scientific journals and articles, as well as by digging from books, journals and scientific articles related to the research object.